Mudcake effects on wellbore stress and fracture initiation pressure and implications for wellbore strengthening - Yongcun Feng (KeAi Communications Co., Ltd., 2018)
Abstract Although a large volume of mudcake filtration test data is available in the literature, effects of mudcake on wellbore strengthening cannot be quantified without incorporating the data into a stress-analysis model. Traditional models for determining fracture initiation pressure (FIP) either consider a wellbore with an impermeable mudcake or with no mudcake at all. An analytical model considering permeable mudcake is proposed in this paper. The model can predict pore pressure and stress profiles around the wellbore, and consequently the FIP, for different mudcake thickness, permeability, and strength. Numerical examples are provided to illustrate the effects of these mudcake parameters. The results show that a low-permeability mudcake enhances FIP, mainly through restricting fluid seepage and pore pressure increase in the near-wellbore region, rather than by mudcake strength. Fluid loss pressure (FLP) should be distinguished from FIP when a mudcake is present on the wellbore wall. Fracture may occur behind the mudcake at FIP without mudcake rupture. The small effect of mudcake strength on FIP does not mean its effect on FLP is small too. Mudcake strength may play an important role in maintaining integrity of the wellbore once a fracture has initiated behind the mudcake.